Hind-limb unloading in rodents: Current evidence and perspectives. (June 2022) - Hawliczek, Anna; Brix, Bianca; Al Mutawa, Shamma; Alsuwaidi, Hanan; Du Plessis, Stefan; Gao, Yunfang; Qaisar, Rizwan; Siddiqui, Ruqaiyyah; Elmoselhi, Adel B.; Goswami, Nandu
Abstract: Due to scarcity of available biological samples from returning space explorers, alternative models, which improve the understanding of spaceflight-related pathophysiology are needed. This review presents an update of available literature on the hind-limb unloading model (HLU). HLU has been used as a model to simulating microgravity in rodents since the early 1980s. This model, by removing the gravitational load from hind limbs of the animals, is widely used for studying the effects of the hindlimb unloading on the cardiovascular and musculoskeletal physiology. Recent updates in the literature with regards to HLU, its advantages as well as how this model can be used to understand the effects of bedrest confinement and/or spaceflight are provided. Highlights: Hind-limb unloading (HLU) is a model to simulating microgravity in rodents. This review represents update of available literature on HLU. Discussed are musculoskeletal, cardiovascular and endothelial changes due to HLU. We further highlight the effects of HLU on immunity, stress and the microbiome.